The optimization of a multilayer structural element in plasto-elastic zone - Kleiza, Vytautas; Bareišis, Jonas (Lietuvos matematikos rinkinys, 2004)
To estimate the efficiency of plasto-elastic strain multilayer rods, a concept of the efficiency coefficient has been introduced. In this paper, it has been proved that, if the efficiency coefficient, as a function of three variables is defined in a rectangular parallelepiped, then both the global minimum and the maximum are in the vertices of this domain.